Reassessment of molecular and morphological variation within the Anagrus atomus species complex (Hymenoptera: Mymaridae): egg parasitoids of leafhoppers (Hemiptera: Cicadellidae) in Europe and North America. Issue 27 (17th July 2020) - Triapitsyn, Serguei V.; Rugman-Jones, Paul F.; Tretiakov, Peter S.; Daane, Kent M.; Wilson, Houston
ABSTRACT: Members of the Anagrus atomus (L.) (Hymenoptera: Mymaridae) species complex within the atomus species group of the nominate subgenus of Anagrus Haliday are common egg parasitoids of typhlocybine leafhoppers (Hemiptera: Cicadellidae: Typhlocybinae) in grape and other agroecosystems in Europe and North America. Here, all the species in this complex are reassessed using both molecular and morphometric methods. Findings indicate that this complex includes A. erythroneurae S. Trjapitzin and Chiappini syn. n., A. lindberginae Nugnes and Viggiani syn. n., A. nepetellae Viggiani and Nugnes syn. n., A. parvus Soyka syn. n., and A. ustulatus Haliday syn. n., all of which are synonymised with A . ( Anagrus ) atomus based on the presented genetic evidence. We consider the slight morphological differences among these nominal species to be at most due to intraspecific, rather than interspecific, variability. As such, populations of A. atomus in the New World (the Nearctic region, Argentina, and Chile) and New Zealand, where it is likely not native, appear to be the result of inadvertent spread with agricultural crops and other plants by European settlers.